On some degree-based irregularity indices of certain networks. (17th February 2021) - Vignesh, R.; Thanga Rajeswari, K.; Venkatesh, S.; Natarajan, C.; Alaeiyan, Mehdi
Abstract: Irregularity indices are a special type of topological indices, first studied by Paul Erdös In this paper, we compute twelve degree-based irregularity topological indices for some networks like Butterfly networks, BF(r), Benes networks B(r), two important mesh derived networks namely MDN1, MDN2 with respect to the edge partition obtained for each such networks.